2017
DOI: 10.1097/mog.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem/stromal cell therapy for inflammatory bowel disease

Abstract: Recent studies demonstrate that MSCs are well tolerated and have an excellent short-term efficacy for the management of refractory fistulizing perianal Crohn's disease. The current data suggest that its influence may 'wear off' over time. More data on larger number of patients with longer duration of follow-up in the setting of a randomized placebo controlled trial are needed to confirm these promising results. For luminal IBD, there is a need for more mechanistic studies in representative preclinical murine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Colitis, an inflammation of the colon, was treated with using intraperitoneal injection 10 5 -10 6 human ADSCs or murine ADSCs in a study[ 56 , 57 ]. This study was associated with reduced weight loss, improved survival and improved clinical in ADSC groups[ 57 ].…”
Section: Colitis Diseasementioning
confidence: 99%
“…Colitis, an inflammation of the colon, was treated with using intraperitoneal injection 10 5 -10 6 human ADSCs or murine ADSCs in a study[ 56 , 57 ]. This study was associated with reduced weight loss, improved survival and improved clinical in ADSC groups[ 57 ].…”
Section: Colitis Diseasementioning
confidence: 99%
“…Due to the intrinsic regenerative potential and immunomodulatory abilities, the stem cells (SCs) therapy has opened up a breakthrough approach to cure autoimmune disease. Meta-analyses of studies on SCs therapy indicated a certain potential to treat liver cirrhosis [3][4][5], chronic liver disease [6], inflammatory bowel disease [7] and ischemic heart disease [8]. SCs therapy also showed a potential effect to halt or abolish the autoimmune destruction of β cells and to generate functional β cells which could achieve optimized glycemic control in T1DM [9][10][11][12][13].…”
mentioning
confidence: 99%
“…Recently, limitations of MSCs have been reported. For example, therapeutic effects were not long term and were affected by inflammatory condition [ 59 , 60 ]. Thus, the results of ongoing clinical studies will be expected to provide further insights.…”
Section: Resultsmentioning
confidence: 99%